Flexible Regions within IκBα Create the Ubiquitin-independent Degradation Signal - Mathes, Erika (American Society for Biochemistry and Molecular Biology, 2010)
Homeostatic regulation of NF-κB requires the continuous synthesis of IκBα and its rapid degradation by the proteasome through a ubiquitin-independent pathway. We previously showed that the ubiquitin-independent degradation signal of unbound IκBα was located in the C-terminal PEST region, and we have now identified a single tyrosine, Tyr-289, and determined that the hydrophobic character of the tyrosine is important for the rapid turnover of IκBα. The sequence composition of the PEST peptide surrounding this Tyr-289 imposes a distinct polyproline II conformation. Enhancing the polyproline II helix formation correlates with slower degradation rates of unbound IκBα. We have further identified a degradation signal located within the 5th ankyrin repeat that is functional once the C terminus is removed. Both the C-terminal and 5th ankyrin repeat degradation signals have inherent flexibility and specific hydrophobic residue(s), which together constitute the ubiquitin-independent degradation signal for IκBα.